2013
DOI: 10.1111/inm.12054
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and coping strategies among Jordanian nursing students during clinical practice in psychiatric/mental health courses

Abstract: Clinical practice in the psychiatric/mental health nursing (PMHN) field is considered a highly-stressful experience for nursing students. The purpose of the present study was to identify the degrees of stress, the types of stressors, and coping strategies perceived by undergraduate nursing students during their clinical practice in PMHN courses. A descriptive, longitudinal design was used. Sixty-five students registered in PMHN clinical courses were recruited from five Jordanian universities using a systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
99
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 40 publications
15
99
2
5
Order By: Relevance
“…This questionnaire was translated into Arabic language and published by Alzayyat and AlGamal in 2014 [5]. The Arabic version questionnaire was used as it is the mother tongue language for Saudi nursing students.…”
Section: Instrumentmentioning
confidence: 99%
“…This questionnaire was translated into Arabic language and published by Alzayyat and AlGamal in 2014 [5]. The Arabic version questionnaire was used as it is the mother tongue language for Saudi nursing students.…”
Section: Instrumentmentioning
confidence: 99%
“…Therefore, they should help the students to adapt to the clinical setting in a supportive manner, and endeavor to produce a student friendly clinical setting with nursing staff Al-Zayyat& Al-Gamal (27) .In the present study the student reported that clinical nurse educators unconcern to improve communication between nursing staff and faculty members. This mean that the nursing students felt that support from the clinical staff and faculty had an impact on their learning.…”
Section: Resultsmentioning
confidence: 70%
“…Edwards, et al; Subhi AlZayyat and Al-Gamal [51,58] disagreed with the study result as they stated that problem focused strategy was the most utilizing coping strategy by nurses and social support was the least-used one. Furthermore, Deklava, Circenis, and Millere [59] revealed that the most coping strategies among nurses were problem solving and self-controlling.…”
Section: Mean Sd the Most Used Coping Strategiesmentioning
confidence: 78%